2017
DOI: 10.1016/j.fgb.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Piperine inhibits aflatoxin B1 production in Aspergillus flavus by modulating fungal oxidative stress response

Abstract: Aspergillus flavus, a soil-borne pathogen, represents a danger for humans and animals since it produces the carcinogenic mycotoxin Aflatoxin B1 (AFB1). Approaches aiming the reduction of this fungal contaminant mainly involve chemicals that may also be toxic. Therefore, identification and characterization of natural antiaflatoxigenic products represents a sustainable alternative strategy. Piperine, a major component of black and long peppers, has been previously demonstrated as an AFB1-inhibitor; nevertheless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 56 publications
(59 reference statements)
5
70
0
Order By: Relevance
“…After treatment with 3.5% ethanol, all catalase genes including Cat, Cat1, Cat2, CatA, and Cu, Zn superoxide dismutase gene sod1 were up-regulated, while only Mn superoxide dismutase gene mnSOD was down-regulated. Similarly, piperine exposure significantly induced decreased expression of veA together with the overexpression of several bZIP transcription factors genes like atfA, atfB, and ap-1 and genes encoding catalase such as catA, cat2, and superoxide dismutase like sod1 in A. flavus (Caceres et al, 2017). Moreover, this gene response was coupled with an obvious increase of catalase enzymatic activity (Caceres et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…After treatment with 3.5% ethanol, all catalase genes including Cat, Cat1, Cat2, CatA, and Cu, Zn superoxide dismutase gene sod1 were up-regulated, while only Mn superoxide dismutase gene mnSOD was down-regulated. Similarly, piperine exposure significantly induced decreased expression of veA together with the overexpression of several bZIP transcription factors genes like atfA, atfB, and ap-1 and genes encoding catalase such as catA, cat2, and superoxide dismutase like sod1 in A. flavus (Caceres et al, 2017). Moreover, this gene response was coupled with an obvious increase of catalase enzymatic activity (Caceres et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…In the meantime, AFs biosynthesis is thought to protect the fungus against oxidative stress (Wang et al, 2019). Several previous studies have indicated that some AFs inhibitors can regulate the stress response system of fungi (Reverberi et al, 2005;Grintzalis et al, 2014;Sun et al, 2015;Caceres et al, 2017). After treatment with 3.5% ethanol, all catalase genes including Cat, Cat1, Cat2, CatA, and Cu, Zn superoxide dismutase gene sod1 were up-regulated, while only Mn superoxide dismutase gene mnSOD was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The aflatoxin production and fungal growth were inhibited by piperine in a dose-dependent manner. Expression analysis of the AF gene cluster demonstrated that almost all genes were down regulated (Caceres et al, 2017). Exposure to piperine also resulted in decreased transcript levels of the global regulator veA together with an overexpression of genes coding several basic leucine zipper (bZIP) transcription factors such as atfA, atfB and ap-1 and genes belonging to superoxide dismutase and catalase families (Caceres et al, 2017).…”
Section: Essential Oils Polyphenols and Alkaloidsmentioning
confidence: 99%
“…Expression analysis of the AF gene cluster demonstrated that almost all genes were down regulated (Caceres et al, 2017). Exposure to piperine also resulted in decreased transcript levels of the global regulator veA together with an overexpression of genes coding several basic leucine zipper (bZIP) transcription factors such as atfA, atfB and ap-1 and genes belonging to superoxide dismutase and catalase families (Caceres et al, 2017). In total, 366 and 87 genes of A. flavus were significantly up-and down-regulated, respectively, when the fungus underwent exposure to resveratrol, a polyphenol isolated from red wine .…”
Section: Essential Oils Polyphenols and Alkaloidsmentioning
confidence: 99%
“…Interestingly, bZIP transcription factor Yap-1Leu558Trp substitution in A. flavus is confirmed as being responsible for voriconazole-resistant phenotypes [32]. When A. flavus was exposed to piperine, transcript levels of bZIP transcription factors atfA, atfB and ap-1 were increased [33]. Genome analysis of A. flavus identified 22 bZIP-type TFs [34], however, the functions of most bZIP-type TFs are still not clear.In this study, the ortholog gene of bZIP-type TF rsmA, termed AflRsmA, was deleted and functionally characterized in A. flavus.…”
mentioning
confidence: 99%